Cystic Echinococcosis: A Case of Extrahepatic Intra-Abdominal Involvement - Patrícia Leitão; André Carvalho; Teresa Fernandes; José Gonçalves (Case Reports in Radiology)
Hydatid disease, or echinococcal disease, is a parasitic infestation caused by the larval stage of the Echinococcus tapeworm and it primarily affects the liver and lung but involvement of other organs is also possible secondary to peritoneal seeding or hematogeneous dissemination. We describe a rare case of extensive abdominal disease, with lesions affecting the liver, peritoneum, and lesser omentum, requiring aggressive surgical intervention. Complementary diagnostic exams were crucial to reach the diagnosis and evaluate the extension of the disease.